Keragaan Karakter Agronomis Galur-galur Jagung Manis (Zea mays L.saccharata Sturt) Var. MS-Unsika Iradiasi Sinar Gamma pada Generasi M1 - Muhammad Syafi'i; Fatimah Azzahra (Faculty of Agriculture University of Singaperbangsa Karawang, 2020)
Sweet corn is a horticultural commodity that has a high carbohydrate source. The need for this commodity continues to increase every year, while the production results produced by farmers have not been able to meet those needs. Efforts need to be made to increase the production of sweet corn, one of the efforts that can be done is to utilize mechanical technology, the use of mutation techniques in corn plants to assemble the genetic traits of varieties through mutations with radiation. This research aims to get the best treatment between sweet corn lines and gamma ray irradiation dose on yield components. This research was carried out in PT. Pertani, Telukjambe Karawang District start in May 2019 until September 2019.The research method used was an experimental method using factorial randomized block design. There are two factors consisting of 20 treatments. The first factor is sweet corn strain consisting of 5 lines, namely MS-09, MS-010, MS-011, MS-012 and MS-014. The second factor is the dose of gamma ray irradiation which consists of 4 levels, namely M0 (0 gy), M1 (100 gy), M2 (200 gy) and M3 (300 gy). Each treatment was repeated 2 times so that in total there were 40 experimental units. The effect of the treatment was analyzed by variance and if the F test level of 5% was significant, then to find out the best treatment continued with a further DMRT (Duncan Multiple Range Test) test at the 5% level. There is an treatment effect between sweet corn genotype and gamma ray irradiation dose, the best effect is on the treatment of G7M1 (strain MS-010 and irradiation dose 100 gy) in all parameters of observation, weight of cob with kelobot (192.02 gr), weight of cob without cob (133.12 gr), length of ear with cob (192.12 gr) 26.19 cm), the length of the ear without cob (17.35 cm), and the diameter of the ear without cob (4.16 cm).